2017
DOI: 10.1590/s0100-204x2017000900012
|View full text |Cite
|
Sign up to set email alerts
|

Wheat yield in the Cerrado as affected by nitrogen fertilization and inoculation with Azospirillum brasilense

Abstract: -The objective of this work was to evaluate the effect of inoculation with Azospirillum brasilense, associated with N rates and sources, in soil of the Cerrado (Brazilian savanna), on the grain yield of irrigated wheat (Triticum aestivum). The experiment was carried out under a no-tillage system in a Typic Haplustox. The experimental design was randomized complete blocks with four replicates, in a 2x5x2 factorial arrangement: two N sources (urea and urea with NBPT urease inhibitor); five N rates applied as top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 20 publications
6
40
0
6
Order By: Relevance
“…However, the increase in grain yield, independently of forms of inoculation, was equivalent to 16.1% compared to control. Similar results were reported in the literature where wheat yield was between 3.1% and 11.1% greater in inoculated plants compared with non-inoculated plants [10,[56][57][58]. Fukami et al [11] reported that spray inoculation with A. brasilense either on leaves or soil can increase plant growth and can replace 25% of N fertilization on grasses.…”
Section: Discussionsupporting
confidence: 80%
“…However, the increase in grain yield, independently of forms of inoculation, was equivalent to 16.1% compared to control. Similar results were reported in the literature where wheat yield was between 3.1% and 11.1% greater in inoculated plants compared with non-inoculated plants [10,[56][57][58]. Fukami et al [11] reported that spray inoculation with A. brasilense either on leaves or soil can increase plant growth and can replace 25% of N fertilization on grasses.…”
Section: Discussionsupporting
confidence: 80%
“…Quanto ao sistema radicular, observou-se que a inoculação de A. brasilense promoveu aumento do comprimento das raízes da cevada, porém não influenciou no volume e na massa seca das raízes (Tabela 7). Esses efeitos podem estar associados a capacidade da bactéria em promover o aumento da disponibilização de alguns nutrientes para as plantas, como o nitrogênio e o fósforo, o que pode ter promovido o crescimento radicular (GALINDO et al, 2016;GALINDO et al, 2017). De acordo com Silveira et al (2016), a inoculação com A. brasilense promove o crescimento das raízes de trigo, pela capacidade das mesmas em sintetizar ácido indolacético e fixar nitrogênio.…”
Section: Methodsunclassified
“…Na cultura do trigo, a inoculação da bactéria melhorou o teor de clorofila e promoveu o peso das raízes (SILVEIRA et al, 2016), aumentando a altura das plantas e o número de grãos por espiga da cultura (ALVES et al, 2017). No milho, essa bactéria pode aumentar a produtividade de grãos (MORAIS et al, 2016).…”
Section: Introductionunclassified
“…Soybean (Glycine max (L.) Merrill) occupied 35,866 million hectares in the 2018/2019 season, with average grain yield of 3,207 kg ha -1 (CONAB, 2019). To obtain high yields of soybean grains and considering the nitrogen (N) demand of this crop, the biological fixation of N must work at maximum efficiency (Galindo et al, 2017;Moretti et al, 2018). In this context, the use of new technologies seeking to increase seed yield and quality becomes essential for the competitive agriculture and low carbon emissions (Sá et al, 2017).…”
Section: Introductionmentioning
confidence: 99%